The Evidence Does Not Lie: A Forensic Investigation Program to Bridge the Gaps Between Crime Scene Investigation and Forensic Science - Fish, Jacqueline Trinkle (2004)
There is a heightened pubic awareness of the importance of forensic science to crime scene investigation. This study examined current graduate programs in forensic science and criminal justice in the United States to determine if higher education provides curricula that meets the needs of crime scene investigators. Using data collected from an online questionnaire, interviews, and a literature review, the researcher examined the perceptions of 51 crime scene investigators and practitioners affiliated with the National Forensic Academy at The University of Tennessee. The data gathered was used to identify and rank the skills most important for accurate processing and collection of physical evidence at the crime scene. Practitioners were also asked to determine course topics that should be integrated in a multidisciplinary graduate forensic investigation program. There are only four universities that offer graduate programs that have acknowledged the need for a program designed for crime scene investigators. An analysis of the four programs revealed that less than half of the knowledge, skills, and abilities identified by practitioners as essential to the performance of their job responsibilities have been incorporated into current curricula. The conclusion is that there exists a gap between the disciplines of criminal justice and forensic science that has not been adequately addressed by graduate programs. The implementation of a graduate forensic investigation program is suggested as a means of bridging the existing gap between the disciplines. As a result of the research, a model curriculum is proposed in the dissertation that integrates technological advances in forensic sciences and provides the knowledge, skills, and abilities to meet the needs of crime scene investigators